(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2024)
The research aims to investigate the impact of information technology governance on reducing the risks of cloud-based accounting information systems. With significant advancements in information technology and cloud computing in recent years, cloud-based accounting systems have become a common solution for managing accounting information and data in companies and organizations. The researchers prepared a questionnaire A total of (110) questionnaires were distributed to a sample of banks, and (100) of them were collected, and it was found that (92) of them were suitable for analysis. (8) were excluded due to their unsuitability for use. The statistical analysis program (SPSS) was used, as the arithmetic mean, standard deviation, proportions, frequencies, linear regression, correlation and influence coefficient were used, and a five-point Likert scale was adopted in formulating the questions, to perform the necessary statistical analyses The research reached results, the most important of which is that there is a relationship and influence between information technology governance and cloud accounting information systems. As the use of these systems increases, the importance of the issue of governance in ensuring information security and reducing potential risks increases as information technology governance seeks to achieve the company’s goals and ensure the safety and sustainability of information systems. And address potential challenges and risks related to information security, privacy, and control of financial data.